lncRNAs and circRNAs: Emerging Players in Pediatric Medulloblastoma Pathology - Beylerli, Ozal; Musaev, Elmar; Ilyasova, Tatiana; Sufianov, Albert (Current Medicinal Chemistry, 2025)
Medulloblastomas (MBs) are the most common malignant brain tumors in children, marked by aggressive growth, molecular heterogeneity, and a high propensity for cerebrospinal dissemination. Despite advancements in conventional treatments - surgery, chemotherapy, and radiation therapy—substantial challenges persist, including debilitating long-term toxicities and emerging resistance to therapy. This review examines the multifaceted roles of non-coding RNAs (ncRNAs) - particularly long non- coding RNAs (lncRNAs) and circular RNAs (circRNAs) - in pediatric medulloblastoma pathogenesis, diagnosis, and therapeutic targeting. NcRNAs exert robust regulatory effects on gene expression by modulating signaling pathways, acting as miRNA sponges, and controlling the expression of oncogenic or tumor-suppressive genes. In this study, we focus on notable examples of lncRNAs (<span class=
Keywords: circRNAs